KESIAPAN GURU DALAM MENGIMPLEMENTASIKAN ASESMEN DIAGNOSTIK PADA PEMBELAJARAN MATEMATIKA DI SMP NEGERI 4 TONDANO - Damopolii, Matthew Clay Immanuel; Pulukadang, Rosiah Juliati; Pitoy, Cori (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aims to determine teachers’ readiness in implementing diagnostic assessment in mathematics learning at SMP Negeri 4 Tondano. This research employed a qualitative approach with a case study design. The subjects of the study consisted of three mathematics teachers who had implemented diagnostic assessment in their teaching. Data collection techniques included in-depth interviews, classroom observations, and documentation of diagnostic assessment instruments and blueprints. The data were then analyzed using the interactive data analysis model by Miles and Huberman, which involves data reduction, data display, and conclusion drawing. To ensure data validity, source and technique triangulation were applied. The results showed that teachers’ readiness falls into the sufficient category. Two teachers (Mathematics Teacher 1 and Mathematics Teacher 2) have understood the concept, developed instruments, implemented, and evaluated diagnostic assessment well, although there are still challenges related to students’ readiness. Meanwhile, one teacher (Mathematics Teacher 3) has not implemented diagnostic assessment formally. The instruments developed include test blueprints and cognitive test items; however, they do not yet fully cover non-cognitive assessment components and comprehensive evaluation instruments